Efectos del cargo por confiabilidad sobre el precio spot de la energía eléctrica en Colombia (2015)
This paper considers the effect of electricity generation reliability on the spot price of the electricity market in Colombia, a mechanism implemented in 2006 to encourage existing generators or new investors to increase the installed capacity in the wholesale energy market. We describe the performance of this mechanism in Colombia and analyze the behavior of some structural variables in the operation of this market, such as the ratio between the market demand and the actual availability, El Niño and La Niña, the reservoir level and some regulation measures. The spot price presents high volatility implying that the proper specification corresponds to a regression model with ARCH structure (Engle, 1982). Results show that the reliability charge is positive and statistically significant. Also El Niño has a positive impact on the spot price, due to the large hydraulic share of this market.